If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying f(x) = (0.7x + 6)(0.4x + -8) Multiply f * x fx = (0.7x + 6)(0.4x + -8) Reorder the terms: fx = (6 + 0.7x)(0.4x + -8) Reorder the terms: fx = (6 + 0.7x)(-8 + 0.4x) Multiply (6 + 0.7x) * (-8 + 0.4x) fx = (6(-8 + 0.4x) + 0.7x * (-8 + 0.4x)) fx = ((-8 * 6 + 0.4x * 6) + 0.7x * (-8 + 0.4x)) fx = ((-48 + 2.4x) + 0.7x * (-8 + 0.4x)) fx = (-48 + 2.4x + (-8 * 0.7x + 0.4x * 0.7x)) fx = (-48 + 2.4x + (-5.6x + 0.28x2)) Combine like terms: 2.4x + -5.6x = -3.2x fx = (-48 + -3.2x + 0.28x2) Solving fx = -48 + -3.2x + 0.28x2 Solving for variable 'f'. Move all terms containing f to the left, all other terms to the right. Divide each side by 'x'. f = -48x-1 + -3.2 + 0.28x Simplifying f = -48x-1 + -3.2 + 0.28x Reorder the terms: f = -3.2 + -48x-1 + 0.28x
| 2(3x-4)=(4x+3) | | x+5=2(5x-2) | | 2(x-5)-21=0 | | 7=6(x+6)+8x | | -27=-7+4v | | 4=-7/2•5 | | 3(2x+10)=40 | | (-6x/4)=5 | | 10x+10=12x-6 | | 2+1.25=10-2.75x | | 4(7+5)=16 | | 2x-10y(-4)=20 | | x^2-5y^2+4x-10y+4=0 | | v^2-10v-96=0 | | (-27x^3)(y)/(9x^4)(y) | | 2(2g+3)=38 | | 2x-2y+5z-2x-y+3z= | | 5cosx+6cosx-8=0 | | 3^14k7/2^19 | | 2(3x+1)=4(x+5) | | P^2+20p-3500=0 | | 5(2+1)=50 | | 0.71428571y-15=5y+30 | | 5(10x+1)=12 | | 8-3x=-x-2 | | 3n^2-3n-9=0 | | n^2+16n-76=0 | | 54=43+v | | 4x^3-1/x^2 | | 2k^2+6k-1=0 | | 2Y=-6x-5/3 | | 3t+5=14 |